Sexual crime: victims and survivors - Winder, Belinda; Hocken, Kerensa; Lievesley, Rebecca; Harper, Craig A.; Blagden, Nicholas; Swaby, Helen; Banyard, Phil (Sexual crime, 2024)
This book offers an original contribution drawing together literature, research, practitioner and service user perspectives around the victimology of sexual crime and offending. Texts about sexual crime focus on the perpetration of sexual crime. This is important as, if we know how, why and in what situations people commit abuse, it will help us prevent further suffering. However, it is important that the voices of people who have experienced sexual abuse are heard and understood, as there is much we can learn from them - not simply about their experiences but improving our knowledge of victimisation also informs how we prevent sexual crime. Belinda Winder is Professor of Forensic Psychology and Head of the Sexual Offences, Crime and Misconduct Research Unit at Nottingham Trent University, UK. She is a co-founder of the Safer Living Foundation charity. Kerensa Hocken is a registered forensic psychologist at HMPPS Whatton, UK. She has oversight for the assessment and treatment of people in prison for sexual offending in the Midlands region. Rebecca Lievesley is Senior Lecturer in Psychology at Nottingham Trent University, UK and has conducted research within the criminal justice system for many years. Craig Harper is Senior Lecturer in Psychology at Nottingham Trent University, UK. He specializes in topics related to forensic and political psychology. Nicholas Blagden is Associate Professor and co-leads the Sexual Offences, Crime and Misconduct Research Unit at Nottingham Trent University, UK. He is a co-founder of the Safer Living Foundation charity. Helen Swaby is Lecturer in Counselling at Bishop Grosseteste University, UK. She is a qualified integrative psychotherapist and has a background in forensic psychology research. Phil Banyard is Head of Psychology at Nottingham Trent University, UK. He was honoured with the British Psychological Societys Award for Distinguished Contributions to Psychology Education